Online teaching-learning in higher education during the lockdown period of the COVID-19 pandemic / Dr. Roshidah Safeei and Hawa Syamsina Md Supie - Safeei, Roshidah; Md Supie, Hawa Syamsina (Universiti Teknologi MARA, Kedah, 2023)
The Novel Coronavirus Disease 2019 (COVID-19) has caused the closure of the whole educational system from kindergarten to tertiary levels worldwide. This study presents a qualitative study that examines the various forms of online distance learning modes adopted during the COVID-19 pandemic by lecturers in the Faculty of Accountancy, Universiti Teknologi MARA Kedah. This paper seeks to find out the perceptions of lecturers and students on online distance learning and the challenges faced by them during the COVID-19 pandemic. All lecturers and students of the Faculty of Accountancy, Universiti Teknologi MARA Kedah were the population of the study and they the interviewees were sampled using convenience sampling technique. This study is descriptive and exploratory in nature, with the data obtained from a semi-structured interview. The findings revealed that the major challenge during online distance learning was the unstable internet connection. The findings is significant in helping lecturers and educational institutions to understand students’ challenges regarding online learning. Higher education institutions are recommended should consider and solve the challenges faced by lecturers and students.